O material manipulável Algeblocks: uma proposta para o ensino médio - Camargo, Alex Sander Martins de (Universidade Federal de São Carlos, 2020)
This work had the purpose of developing an educational product in the form of a teaching proposal for the algebra of high school grades. More specifically, to propose studies of algebraic content through the use of concrete manipulative material called Algeblocks. Given the theoretical and methodological support of the exploratory-investigative tasks proposed by João Pedro da Ponte and his collaborators, in addition to the figurative representations of Efraim Fischbein, four tasks were planned, involving the following contents: second degree function; concepts of regular polygons; resolution, analysis and discussion of linear systems with two equations and two variables using scaling; approach to prism concepts (surface area and volume) and Euler relationship. For each of the tasks, a possible resolution script was presented, articulated with the theoretical frameworks presented in this research. In terms of the potential of didactic material, we highlight that it is a relevant resource for the establishment of representation records, both geometric and algebraic; versatile for use in elementary and high school content. A reflection on the limitations of the material is that it does not guarantee the validity of mathematical statements in a mathematical investigation.

Este trabajo tenía el propósito de desarrollar un producto educativo en forma de una propuesta de enseñanza para el álgebra de los grados de secundaria. Más específicamente, proponer estudios de contenido algebraico a través del uso de material manipulador concreto llamado Algeblocks. Dado el apoyo teórico y metodológico de las tareas exploratorias-investigativas propuestas por João Pedro da Ponte y sus colaboradores, además de las representaciones figurativas de Efraim Fischbein, se planificaron cuatro tareas, que incluyen los siguientes contenidos: función de segundo grado; conceptos de polígonos regulares; resolución, análisis y discusión de sistemas lineales con dos ecuaciones y dos variables usando escalado; aproximación a los conceptos de prisma (superficie y volumen) y relación de Euler. Para cada una de las tareas, se presentó un posible guión de resolución, articulado con los marcos teóricos presentados en esta investigación. En términos del potencial del material didáctico, destacamos que es un recurso relevante para el establecimiento de registros de representación, tanto geométricos como algebraicos; versátil para usar en contenido de primaria y secundaria. Una reflexión sobre las limitaciones del material es que no garantiza la validez de los enunciados matemáticos en una investigación matemática.

Ce travail avait pour objectif de développer un produit pédagogique sous forme de proposition pédagogique pour l'algèbre des lycées. Plus précisément, proposer des études de contenu algébrique à travers l'utilisation de matériel de manipulation concret appelé Algeblocks. Compte tenu du soutien théorique et méthodologique des tâches exploratoires-d'investigation proposées par João Pedro da Ponte et ses collaborateurs, en plus des représentations figuratives d'Efraim Fischbein, quatre tâches étaient prévues, impliquant les contenus suivants: fonction de second degré; concepts de polygones réguliers; résolution, analyse et discussion de systèmes linéaires avec deux équations et deux variables en utilisant l'échelle; approche des concepts de prisme (surface et volume) et relation d'Euler. Pour chacune des tâches, un script de résolution possible a été présenté, articulé avec les cadres théoriques présentés dans cette recherche. En termes de potentiel du matériel didactique, nous soulignons qu'il s'agit d'une ressource pertinente pour l'établissement des enregistrements de représentation, à la fois géométrique et algébrique; polyvalent pour une utilisation dans le contenu du primaire et du secondaire. Une réflexion sur les limites du matériau est qu'il ne garantit pas la validité des énoncés mathématiques dans une investigation mathématique.
The manipulable material Algeblocks: a proposal for high school
El material manipulable Algeblocks: una propuesta para el instituto
Keywords: Algeblocks; Conceitos figurais; Material manipulável; Representações figurais; Tarefas exploratório-investigativas; Figurative concepts; Manipulated material; Figurative representations; Exploratory-investigative tasks; CIENCIAS EXATAS E DA TERRA::MATEMATICA